Formal synthesis of (+)-didemniserinolipid B employing a Pd-mediated 6-endo selective alkynediol cycloisomerization - Ramana, C. V.; Induvadana, Boddeti (Tetrahedron Letters, 2009)
Herein, we describe a concise assembly of central 6,8-dioxabicyclo[3,2,1]octane core of didemniserino-lipid by employing a Pd-mediated alkynediol cycloisomerization and a formal total synthesis of didemniserinolipid (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Didemniserinolipid; Yamaguchi oxirane alkyne coupling; Zipper reaction